Black Carbon Aerosols in the Lower Free Troposphere are Heavily Coated in Summer but Largely Uncoated in Winter at Jungfraujoch in the Swiss Alps. Issue 14 (23rd July 2020) - Motos, Ghislain; Corbin, Joel C.; Schmale, Julia; Modini, Rob L.; Bertò, Michele; Kupiszewski, Piotr; Baltensperger, Urs; Gysel‐Beer, Martin
Abstract: Black carbon (BC) particles are responsible for substantial radiative heating of the atmosphere. However, the climate‐relevant properties of BC particles in the free troposphere (FT) are poorly constrained over longer time scales. Here, we report on in situ, intensive field campaigns deploying a single‐particle soot photometer during summer and winter seasons at the Jungfraujoch (3, 580 m a.s.l., Switzerland), a site often located in the lower FT. The refractory BC (rBC) mass size distribution was very stable across the two seasons. BC was generally internally mixed (i.e., heavily coated with other aerosol material) in summer. However, against general expectations, BC was predominantly externally mixed in winter, with a high occurrence of negligibly‐to‐thinly coated BC. This strong seasonality in lower‐FT BC mixing state has not been previously observed and would substantially influence the lifetime, loading, and climate effects of free‐tropospheric BC. Future measurements should investigate the generality of these results. Plain Language Summary: Black carbon (BC) aerosols (i.e., soot particles) play an important role in global climate change by causing atmospheric warming. To understand this role, we need to know what types of BC particles are found in the atmosphere; how big are they and how are they mixed with other aerosols? This type of information is lacking for BC particles found in the free troposphere (the atmospheric layer immediately above the mixed boundary layer of air at the Earth's surface). We performed measurements during winter and summer seasons at Jungfraujoch in the Swiss Alps (3, 580 m a.s.l.) in order to fill this gap in knowledge. We discovered a large and unexpected seasonal contrast; in summer at this site, BC aerosols are heavily coated with other aerosol material, whereas in winter the BC is largely uncoated. This seasonal contrast has important implications for our understanding of how long BC particles stay in the atmosphere (coated particles are removed faster), and our estimates of BC climate impacts (coated particles absorb more sunlight). Key Points: Laser‐induced‐incandescence measurements revealed no seasonal variability in black carbon (BC) mass size distributions at Jungfraujoch BC was heavily coated in summer but largely uncoated in winter, a seasonality that has not been reported before These measurements have important implications for the aging timescales and lifetime of BC in the free troposphere